تحضير قهوة مالت الشعير ودراسة بعض خصائصها الكيميائية ومقارنتها مع القهوة العادية من الناحية الحسية - اسعيد, مصطفى; علي, علي; صالح, شذا (Latakia University Journal -Biological Sciences Series, 2018)
In this research, a barley malt coffee has been produced after germination, drying and roasting, so It can be a substitute traditional coffee for economic and health reasons. Tasting tests has been done for barley malt coffee drink samples roasted at 200 ° C for (32, 30, 28) minutes. Tastes were done according to the CoffeeGeek taste model, which is one of the internationally approved models for evaluation coffee taste. Twenty of coffee drink lovers did the evaluations. Barely malt coffee roasted at 200 ° C for 32 minutes was tilted as the best and closest to traditional coffee. Many tests were conducted on raw barley and barley malt samples and the effect of roasting on barley malt in terms of some characteristics, As well as we studied the ratio of dissolved solids in 10% barley malt coffee drink and the PH. تمَّ في هذا البحث إنتاج قهوة من مادة الشعير بعد إنباته وتجفيفه (مالت الشعير) وتحميصه لتكون بديلاً عن القهوة العادية لإسباب اقتصادية وصحية. أُجريت اختبارات التذوق لشراب قهوة مالت الشعير بعد تحميصه عند الدرجة 200مْ ولمدة(32,30,28) دقيقة وفق نموذج Coffee Geek للتذوق وهو نموذج من ضمن مجموعة نماذج معتمدة عالمياً لتقييم مذاق القهوة. تمَّ التقييم من قبل عشرين شخص من المحبين لشراب القهوة. وأظهرت النتائج بأن قهوة مالت الشعير المحمصة عند الدرجة 200مْ ولمدة 32 دقيقة هي الأفضل والأقرب للقهوة العادية. تمَّ إجراء عدة اختبارات على عينات الشعير الخام ومالت الشعير ودراسة تأثير التحميص على مالت الشعير من ناحية بعض الخصائص، بالإضافة إلى دراسة شراب قهوة مالت الشعير من ناحية نسبة المواد الصلبة المنحلة في شراب محضر بنسبة 10% ، و رقم الـ pH.